2018
DOI: 10.2147/ndt.s160424
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of variants in estrogen receptor genes and perinatal depression

Abstract: ObjectivesDepressive symptoms are common during pregnancy and after childbirth. Estrogen levels fluctuate greatly during the course of pregnancy and may contribute to mood instability. The first aim of this case–control study was to investigate whether variants in the two estrogen receptor genes might contribute to the genetic susceptibility to pregnancy-related depression using controls that were screened for postnatal depression. The second aim was to uncover new variants in the two estrogen receptor genes.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
(35 reference statements)
0
16
0
Order By: Relevance
“…Tsai et al (Tsai et al, 2003) first reported the significant association of rs2234693 in female depression patients and was then identified in the Chinese population by He's study (He et al, 2017). Tan's (Tan et al, 2018) and Ryan's (Ryan et al, 2012) studies also showed a higher frequency of the C allele in the depression group than in the control group. Moreover, a significant difference remained in the subgroup of Asians.…”
Section: Discussionmentioning
confidence: 87%
“…Tsai et al (Tsai et al, 2003) first reported the significant association of rs2234693 in female depression patients and was then identified in the Chinese population by He's study (He et al, 2017). Tan's (Tan et al, 2018) and Ryan's (Ryan et al, 2012) studies also showed a higher frequency of the C allele in the depression group than in the control group. Moreover, a significant difference remained in the subgroup of Asians.…”
Section: Discussionmentioning
confidence: 87%
“…Other studies, however, found no polymorphisms of either ESR1 or ESR2 that were associated with postpartum psychosis. 10…”
Section: Postpartum Psychotic Disordersmentioning
confidence: 99%
“…Other studies, however, found no polymorphisms of either ESR1 or ESR2 that were associated with postpartum psychosis. 10 Postpartum psychoses fall into three categories: mania or mixed episodes with psychotic features, depressive episodes with psychotic features, and nonaffective psychotic episodes. 3 These can occur after one birth (usually the first) and never again or they can recur with every birth (25-50% of the time).…”
Section: Postpartum Psychotic Disordersmentioning
confidence: 99%
“…ESR1 has been reported to be associated with MDD 39 and perinatal depression. 40 , 41 ESR1 was implicated in anxiety-like behaviour and was identified to be a genome-wide risk gene for anxiety. 42 Associations between ESR1 and MDD could have useful preventive and therapeutic implications, and help to lead to more personalized therapies based on one’s genetic profile.…”
Section: Discussionmentioning
confidence: 99%